MATRA‐A: A study on massive transfusion. Issue 8 (26th February 2021) - Ünlü, Aytekin; Yılmaz, Soner; Akbasli, Izzet Turkalp; Karaagac Akyol, Tulay; Akkapulu, Nezih; Tumer, Murat; Ertugrul Oruc, Nigar; Balas, Sener; Goral, Seniz; Topcuoglu, Pervin; Tanriseven, Mustafa; Sayin, Selim; et al.
Abstract : Background: We use massive transfusion in various clinical conditions and it is associated with high mortality. Although some massive transfusion protocols improve patient outcomes, the clinical circumstances requiring it are not well defined. Methods: MATRA‐A is a multicenter retrospective study. Six University and Training Research Hospitals in Ankara participated in the study. We collected clinical data on patients (>18 years) who received massive transfusions (≥10 units/24 h) from 2017 through 2019. Results: Overall, 167 (0·27% of transfused patients) received a massive transfusion of 2586 units of red blood cells (1·5% of total RBCs transfused). The median interquartile range values for RBCs, fresh frozen plasma (FFP) and platelets were 13 (11–176), 16 (9–33) and 4 (0–11), respectively. Surgical patients received 90% of massive transfusions. The most common clinical indications for massive transfusion were cardiovascular diseases (42·6%), trauma (20·3%) and malignancies (11%). FFP: RBC: Platelets ratio was 1·9:1:0·5. The overall and trauma‐related mortality rates were 57·4% and 61·8%, respectively. The hospital mortality rates of trauma patients that received high vs. low ratio (FFP: RBCs > 1:1·5 vs. ≤1:1·5) transfusions were 47·6% and 86·6% and the difference was statistically significant ( P  = 0·03). Conclusion: Cardiovascular diseases and trauma occasion are the most common causes of massive transfusion. It is infrequent in clinical settings and is associated with high mortality rates. Additionally, in massively transfused trauma patients, a high FFP:RBCs ratio seems to be associated with increased survival. Focused prospective studies are required to define the areas that need improvement on a national scale.